2019
DOI: 10.1038/s41386-019-0379-7
|View full text |Cite
|
Sign up to set email alerts
|

Social status and demographic effects of the kappa opioid receptor: a PET imaging study with a novel agonist radiotracer in healthy volunteers

Abstract: Kappa opioid receptors (KORs) have been characterized as an aversive system in the brain and implicated in social behavior in preclinical models. This work investigated the effect of social status on the KOR system in humans using positron emission tomography (PET) imaging with the novel KOR agonist radiotracer [ 11 C]EKAP. Eighteen healthy participants (mean age 41.2 ± 9.3) completed the Barratt Simplified Measure of Social Status (BSMSS), an MRI and an [ 11 C]EKAP PET scan on the High Resolution Research Tom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 68 publications
0
11
0
Order By: Relevance
“…First, a nonlinear transformation grid was estimated between the AAL template and each subject's magnetic resonance (MR) image, using BioImage Suite software (v2.5; http://www.bioimagesuite.com). This nonlinear coregistration algorithm is a method first described in 2001 and subsequently used in multiple studies . Then, the subject's summed PET image (0–10 minutes postinjection) was coregistered to their MR image using a 6‐parameter rigid (linear) registration estimated with a mutual information algorithm (FMRIB's Linear Image Registration Tool, FMRIB Software Library).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, a nonlinear transformation grid was estimated between the AAL template and each subject's magnetic resonance (MR) image, using BioImage Suite software (v2.5; http://www.bioimagesuite.com). This nonlinear coregistration algorithm is a method first described in 2001 and subsequently used in multiple studies . Then, the subject's summed PET image (0–10 minutes postinjection) was coregistered to their MR image using a 6‐parameter rigid (linear) registration estimated with a mutual information algorithm (FMRIB's Linear Image Registration Tool, FMRIB Software Library).…”
Section: Methodsmentioning
confidence: 99%
“…This nonlinear coregistration algorithm is a March 2020 331 method first described in 2001 30 and subsequently used in multiple studies. 29,[31][32][33][34][35] Then, the subject's summed PET image (0-10 minutes postinjection) was coregistered to their MR image using a 6-parameter rigid (linear) registration estimated with a mutual information algorithm (FMRIB's Linear Image Registration Tool, FMRIB Software Library). Please see Figure 1 for a diagram of image registration processing.…”
Section: Imagingmentioning
confidence: 99%
“…Only recently have radiotracers been developed to target KOP receptors, including the agonist tracers [ 11 C]GR103545 and [ 11 C]EKAP and the antagonist tracer [ 11 C]LY2795050. These radiotracers have been evaluated in primates (237–240) and humans (241244).…”
Section: The Opioid Receptor Systemmentioning
confidence: 99%
“…A pilot PET study with the κOR-ligand [ 11 C]GR103545 ( 25 ) did not reveal any binding differences between healthy control and patients suffering from major depression [190]. However, a [ 11 C]EKAP ( 27 ) κOR study in healthy volunteers showed an inverse correlation between social status and [ 11 C]salvinorin A ( 33 ) binding in widespread brain areas, with a special association occurring in brain regions mediating reward or aversion [191]. Given the association between social stress and depression, one might have expected covariance κORs in the two studies.…”
Section: Clinical Studiesmentioning
confidence: 99%